2010
DOI: 10.1186/1476-069x-9-46
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution exposure during critical time periods in gestation and alterations in cord blood lymphocyte distribution: a cohort of livebirths

Abstract: BackgroundToxic exposures have been shown to influence maturation of the immune system during gestation. This study investigates the association between cord blood lymphocyte proportions and maternal exposure to air pollution during each gestational month.MethodsCord blood was analyzed using a FACSort flow cytometer to determine proportions of T lymphocytes (CD3+ cells and their subsets, CD4+ and CD8+), B lymphocytes (CD19+) and natural killer (NK) cells. Ambient air concentrations of 12 polycyclic aromatic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 44 publications
4
50
0
1
Order By: Relevance
“…Overall, the findings of the studies examined in this review support the idea that there are one or more critical windows of allergic and immunologic development in utero and during infancy (30, 36, 45). If climate change conditions – including higher temperatures, higher carbon dioxide concentrations, more intense periods of precipitation, and changes in humidity – lead to higher concentrations, altered timing, or increased allergenicity of ambient outdoor pollen and mold, the prevalence of sensitization or even of allergic symptoms in children could change.…”
Section: Linking Climate Change Aeroallergens and Pediatric Diseasesupporting
confidence: 68%
See 1 more Smart Citation
“…Overall, the findings of the studies examined in this review support the idea that there are one or more critical windows of allergic and immunologic development in utero and during infancy (30, 36, 45). If climate change conditions – including higher temperatures, higher carbon dioxide concentrations, more intense periods of precipitation, and changes in humidity – lead to higher concentrations, altered timing, or increased allergenicity of ambient outdoor pollen and mold, the prevalence of sensitization or even of allergic symptoms in children could change.…”
Section: Linking Climate Change Aeroallergens and Pediatric Diseasesupporting
confidence: 68%
“…The development of the immune system is a lengthy and complex process and exposure to potential allergens could have various impacts at different stages of development (35). One recent study on air pollution supports this concept of windows of vulnerability in humans by showing association of exposure by two air pollutants, particulate matter and polycyclic aromatic hydrocarbons, in early and late gestation with lymphocyte cell distribution (36). …”
Section: Pediatric Allergic Disease and Aeroallergensmentioning
confidence: 89%
“…Additional research from the CHARGE study has shown increased plasma levels of immunoglobulin (Ig) G-4 and reduced concentrations of tumor growth factor-β, related to immune response and inflammatory processes, in plasma of children with autism compared with typically developing controls and children with developmental delay (Ashwood et al 2008; Enstrom et al 2009a, 2009b). Other recent work indicates that exposure to air pollution exposure during pregnancy is associated with changes in IgE and in lymphocytes measured from cord blood, supporting the idea that maternal exposure to air pollution is associated with altered immune profiles in the fetus (Herr et al 2010a, 2010b). Moreover, published evidence links maternal antibodies to fetal brain tissue with a subset of autism cases (Braunschweig et al 2008).…”
Section: Discussionmentioning
confidence: 63%
“…In a human cohort, increased exposure to PAHs and fine particulate matter (PM 2.5 ) in the second month of gestation was associated with lower cord IgE levels and relative increases in CD3 + and CD4 + lymphocytes. Increased exposure to PAH and PM 2.5 in mid- to late pregnancy was associated with opposite findings (22, 23), suggesting that the timing of exposure during gestation may have a distinct effect on B-cell and T-cell-related outcomes relevant to allergic sensitization.…”
Section: Discussionmentioning
confidence: 99%